A dual sgRNA-directed CRISPR/Cas9 construct for editing the fruit-specific β-cyclase 2 gene in pigmented citrus fruits - Salonia, Fabrizio; Ciacciulli, Angelo; Pappalardo, Helena Domenica; Poles, Lara; Pindo, Massimo; Larger, Simone; Caruso, Paola; Caruso, Marco; Licciardello, Concetta (Frontiers in Plant Science, 2022)
CRISPR/Cas9 genome editing is a modern biotechnological approach used to improve plant varieties, modifying only one or a few traits of a specific variety. However, this technology cannot be easily used to improve fruit quality traits in citrus, due to the lack of knowledge of key genes, long juvenile stage, and the difficulty regenerating whole plants of specific varieties. Here, we introduce a genome editing approach with the aim of producing citrus plantlets whose fruits contain both lycopene and anthocyanins. Our method employs a dual single guide RNA (sgRNA)-directed genome editing approach to knockout the fruit-specific β-cyclase 2 gene, responsible for the conversion of lycopene to beta-carotene. The gene is targeted by two sgRNAs simultaneously to create a large deletion, as well as to induce point mutations in both sgRNA targets. The EHA105 strain of Agrobacterium tumefaciens was used to transform five different anthocyanin-pigmented sweet oranges, belonging to the Tarocco and Sanguigno varietal groups, and ‘Carrizo’ citrange, a citrus rootstock as a model for citrus transformation. Among 58 plantlets sequenced in the target region, 86% of them were successfully edited. The most frequent mutations were deletions (from -1 to -74 nucleotides) and insertions (+1 nucleotide). Moreover, a novel event was identified in six plantlets, consisting of the inversion of the region between the two sgRNAs. For 20 plantlets in which a single mutation occurred, we excluded chimeric events. Plantlets did not show an altered phenotype in vegetative tissues. To the best of our knowledge, this work represents the first example of the use of a genome editing approach to potentially improve qualitative traits of citrus fruit.